Changes in Physical Attributes, Activities of Fruit Softening Enzymes, Cell Wall Polysaccharides and Fruit Quality of Jackfruit (Artocarpus heterophyllus Lam.) as Influenced by Maturation and Ripening - Jashanpreet Kaur; Zora Singh; Muhammad Sohail Mazhar; Hafiz Muhammad Shoaib Shah; Andrew Woodward (Horticulturae)
Changes in physicochemical parameters, fruit softening enzymes and cell wall polysaccharides at four different maturation stages were investigated in two jackfruit genotypes (‘Accession 242’, ‘Accession 341’). For the first three maturity stages, fruit were harvested at 90, 110, and 130 days after flowering (Stage I, II and III, respectively), while Stage IV was determined based on the presence of a dull hollow tapping sound. The fruit edible portion and seed percentage increased, whilst the core and rag percentage decreased with advancement in fruit maturation and ripening. The fruit harvested at Stage IV had comparatively higher soluble solids content (SSC), ascorbic acid and flavonoids, along with lower titratable acidity (TA) and phenolics, than other maturity stages. Bulb firmness was higher at Stage I in both genotypes, along with higher total pectin, protopectin and cellulose compared to other maturity stages. The activity of cell wall hydrolases was higher during later maturity stages. Fruit harvested at Stage IV had higher edible portions, carotenoids, flavonoids and SSC, as well as better colour attributes, while those harvested at Stage I exhibited higher phenolics, TA, pectin and cellulose. These findings could serve as a baseline for future research related to the intended use and maturity standardisation of jackfruit.